Symposium introduction: Dynamics of governance and civic engagement - Lee, Eliza; Thynne, Ian (2011)
This introduction sets the scene for the Symposium. It considers the governance value of civic engagement, along with civic engagement as identifiable modes of governance. Such matters are embraced in the subsequent analyses of significant developments and experience in South Korea, the Philippines, Australia, Hong Kong and China. - Reproduced.
Keywords: Public administration